Toward developing consensus on family-centred care: An international descriptive study and discussion. (September 2019) - Al-Motlaq, Mohammad A; Carter, Bernie; Neill, Sarah; Hallstrom, Inger Kristensson; Foster, Mandie; Coyne, Imelda; Arabiat, Diana; Darbyshire, Philip; Feeg, Veronica D; Shields, Linda
Nurses around the world have described family-centred care (FCC) in various ways. With limited evidence regarding its implementation and with dissent among professionals regarding outcomes that are amorphously defined across age groups, systems and global settings, a group of children's nursing experts from around the world collaborated to seek clarification of the terms, deconstruct the elements in the model and describe empirically a consensus of values toward operationally defining FCC. A modified Delphi method was used drawing on expert opinions of participants from eight countries to develop a contemporary and internationally agreed list of 27 statements (descriptors of FCC) that could form the foundation for a measure for future empirical psychometric study of FCC across settings and countries. Results indicated that even among FCC experts, understandings of FCC differ and that this may account for some of the confusion and conceptual disagreement. Recommendations were identified to underpin the development of a clearer vision of FCC.